From an Empty Stomach to Anxiolysis: Molecular and Behavioral Assessment of Sex Differences in the Ghrelin Axis of Rats - Börchers, Stina; Krieger, Jean-Philippe; Maric, Ivana; Carl, Jil; Abraham, Maral; Longo, Francesco; Asker, Mohammed; Richard, Jennifer E.; Skibicka, Karolina P. (Frontiers in Endocrinology, 2022)
Ghrelin, a stomach-produced hormone, is well-recognized for its role in promoting feeding, controlling energy homeostasis, and glucoregulation. Ghrelin’s function to ensure survival extends beyond that: its release parallels that of corticosterone, and ghrelin administration and fasting have an anxiolytic and antidepressant effect. This clearly suggests a role in stress and anxiety. To date, most studies of ghrelin’s effects on anxiety have been conducted exclusively on male rodents. Here, we hypothesize that female rats are wired for higher ghrelin sensitivity compared to males. To test this, we systematically compared components of the ghrelin axis between male and female Sprague Dawley rats. Second, we tested whether they show a different anxiety-like behavior and feeding response to endogenous or exogenous ghrelin. In line with our hypothesis, we show that female rats have higher serum levels of ghrelin and lower levels of the endogenous antagonist LEAP-2, compared to males. Furthermore, circulating ghrelin levels are partly dependent on estradiol; ovariectomy drastically reduces circulating ghrelin levels, which are partly rescued by estradiol replacement. In contrast, orchiectomy does not affect circulating plasma ghrelin. Additionally, females express higher levels of the endogenous ghrelin receptor GHSR1A in brain areas involved in feeding and anxiety, such as the lateral hypothalamus, hippocampus, and amygdala. Moreover, overnight fasting increased GHSR1A expression in the amygdala of females, but not males. To evaluate the behavioral consequences of these molecular differences, male and female rats were tested in the elevated plus maze (EPM), open field (OF), and acoustic startle response (ASR) test after three complementary ghrelin manipulations: increased endogenous ghrelin levels through overnight fasting, systemic administration of ghrelin, or blockade of fasting-induced ghrelin signaling with a GHSR1A antagonist. Here, females exhibit a stronger anxiolytic response to fasting and ghrelin in the ASR, supporting our findings of sex differences in the ghrelin axis. Most importantly, after GHSR1A antagonist treatment, females but not males have an anxiogenic response in the ASR, and a more pronounced anxiogenesis in the EPM and OF compared to males. Consequently, females show stronger behavioral responses to endogenous and exogenous ghrelin manipulations in the realm of anxiety-like behaviors, but not feeding behaviors.